2023
DOI: 10.3390/ma16062207
|View full text |Cite
|
Sign up to set email alerts
|

A Review of Pectin-Based Material for Applications in Water Treatment

Abstract: Climate change and water are inseparably connected. Extreme weather events cause water to become more scarce, polluted, and erratic than ever. Therefore, we urgently need to develop solutions to reduce water contamination. This review intends to demonstrate that pectin-based materials are an excellent route to detect and mitigate pollutants from water, with several benefits. Pectin is a biodegradable polymer, extractable from vegetables, and contains several hydroxyl and carboxyl groups that can easily interac… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
6
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 17 publications
(6 citation statements)
references
References 178 publications
(194 reference statements)
0
6
0
Order By: Relevance
“…Prior studies reported LM pectin extracted from cashew apple pomace (28–46% DE), potato pulp (21.51–37.5%) and sunflower head (36.4–39.2%), 38,50 whereas pectic polysaccharides isolated from dragon fruit peel fractions exhibited higher DE values (51.71–63.74%) 51 . Low methoxy pectin implies that less than 50% of the galacturonic acid residues are methoxylated 52 . The mechanism for gel formation varies between high‐methoxy (HM) and LM pectin.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Prior studies reported LM pectin extracted from cashew apple pomace (28–46% DE), potato pulp (21.51–37.5%) and sunflower head (36.4–39.2%), 38,50 whereas pectic polysaccharides isolated from dragon fruit peel fractions exhibited higher DE values (51.71–63.74%) 51 . Low methoxy pectin implies that less than 50% of the galacturonic acid residues are methoxylated 52 . The mechanism for gel formation varies between high‐methoxy (HM) and LM pectin.…”
Section: Resultsmentioning
confidence: 99%
“…51 Low methoxy pectin implies that less than 50% of the galacturonic acid residues are methoxylated. 52 The mechanism for gel formation varies between high-methoxy (HM) and LM pectin. HM pectin forms a gel at pH 3.5 and high sugar concentrations (>55%), whereas LM pectin gels form in the presence of divalent cations such as Ca 2+ , at pH values between 2 and 6, as well as without the need for sugar for gel formation.…”
Section: Chemical Characterization Of Dksp and Its Fractionsmentioning
confidence: 99%
“…Pectin is the complex polysaccharide group contained in the primary cell wall and intercellular regions of the plants, affecting their flexibility and mechanical strength [31]. As depicted in Figure 2, pectin-based products demonstrate various applications such as food [82], agriculture [121,122], pharmacy and health promotion [13,83], packaging [1,123], water treatment [124] and 3Dprinting [125].…”
Section: Current Trends and Future Outlookmentioning
confidence: 99%
“…Crosslinking with calcium ions is common to achieve this, although other metal ions have also been used. Divalent metal ions, such as Ca 2+ , promote the gelation of pectin [7]. The crosslinks are established between the carboxylate groups (COO − , i.e., non-methyl-esterified residues) of neighboring pectin chains via the Ca 2+ ions, which replace the hydrogen bonds in neat pectin.…”
Section: Introductionmentioning
confidence: 99%
“…Later [12,13], it was suggested that Ca 2+ ions could also establish mono-complexes; that is, Ca 2+ ions can interact with single carboxylate groups. Some reviews have summarized the formation of the "egg-box" model or other possible structures in pectin [7,14]. In addition to Ca 2+ , pectin can also be reticulated by cations such as Zn 2+ .…”
Section: Introductionmentioning
confidence: 99%